Peningkatan Kesadaran Hukum Tentang Partisipasi Masyarakat Dalam Pembangunan Desa Di Kabupaten Luwu Sulawesi Selatan - Marwing, Anita; Halide, Nirwana; N., Zahrum; Wati, Shinta (Madani: Jurnal Pengabdian Ilmiah, 2021)
This service activity explains increasing legal awareness regarding community participation in village development in Luwu district. These activities are carried out in the form of counseling using methods of delivering material, interactive dialogue and solving problems related to village development. Several forms of activities that have been carried out in this program are: counseling about the village law; counseling on village development planning; Assistance training in preparing village development plans that are more participatory in nature. The target of this activity is the people of Cakkeawo village and North Bonelemo village, Luwu Regency, South Sulawesi. Based on the activities that have been carried out, there are several indicators that have been achieved, including: (1) building the commitment of community members to have the courage to convey ideas/suggestions at public forums/village deliberations, especially in terms of planning, budgeting and evaluating development results; (2) developing the commitment of citizen organizations to start practicing and discussing procedures for planning, budgeting and evaluating development results using good procedures; (3) building the commitment of village government officials to be open, responsive and accountable in planning, budgeting and evaluating village development results. Apart from that, there is a counter draft village development plan (RAPBDes) which is prepared in a participatory manner.